Preventing respiratory syncytial virus infections in hospitalized children and adults: should we do better?. Issue 2 (June 2020) - Frange, Pierre; Toubiana, Julie; Parize, Perrine; Moulin, Florence; Scemla, Anne; Leruez-Ville, Marianne
Summary: Objective: To compare the burden of nosocomial and community-acquired respiratory syncytial virus (RSV)-associated acute lower respiratory tract infections (ALRIs) in adult and pediatric patients concomitantly admitted to a French tertiary hospital, and to evaluate the effectiveness of existing infection control measures. Patients and methods: We prospectively included all adult and pediatric patients admitted to Necker hospital (Paris) between October 2018 and February 2019 with a diagnosis of RSV-associated ALRI. We compared characteristics of ALRIs between patients with community-acquired versus nosocomial infections and, in each group, between children and adults. Results: Community-acquired and nosocomial RSV-associated ALRIs were diagnosed in 229 and 11 inpatients, respectively. The burden of community-acquired infections was higher in children than in adults: 2.1% versus 0.2% of the total number of pediatric and adult inpatients, respectively (p < 0.0001); 4.2% versus 0.2% of the total number of hospitalization days in pediatric and adult units, respectively (p < 0.0001). Compared to inpatients with community-acquired ALRIs, those with nosocomial infections were more frequently adults (45.5% versus 2.6%, p = 0.0005) and subjects with at least one chronic complex condition (100.0% versus 41.0%, p < 0.0001). The total number of hospitalization days due to nosocomial ALRIs was higher in adults than in children (0.32% versus 0.11%, p < 0.0001). Conclusions: Nosocomial RSV-associated ALRIs rarely occurred, suggesting a good effectiveness of our infection control strategy. However, the burden of nosocomial infection was higher in adults than in children, suggesting that education and training of healthcare personnel, patients and visitors about the risk of nosocomial RSV infections should be reinforced in adult wards.